2022
DOI: 10.3390/jcm11226638
|View full text |Cite
|
Sign up to set email alerts
|

New Trends and Therapies for Familial Hypercholesterolemia

Abstract: Familial hypercholesterolemia (FH) is associated with an elevated risk of atherosclerosis. The finding of monogenic defects indicates higher atherosclerotic risk in comparison with hypercholesterolemia of other etiologies. However, in heterozygous FH, cardiovascular risk is heterogeneous and depends not only on high cholesterol levels but also on the presence of other biomarkers and genes. The development of atherosclerosis risk scores specific for heterozygous FH and the use of subclinical coronary atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 87 publications
0
6
0
2
Order By: Relevance
“…The orally bioavailable PCSK9 inhibitor MK-0616 is currently being developed and may be indicated for patients who cannot comply with monoclonal antibody and inclisiran injection subcutaneously 68 . It has passed phase 1 trials in 60 healthy volunteers with no adverse effects and shown up to 60% reductions in LDL-C after eight weeks in step 2a trials 69 , 70 .…”
Section: Methodsmentioning
confidence: 99%
“…The orally bioavailable PCSK9 inhibitor MK-0616 is currently being developed and may be indicated for patients who cannot comply with monoclonal antibody and inclisiran injection subcutaneously 68 . It has passed phase 1 trials in 60 healthy volunteers with no adverse effects and shown up to 60% reductions in LDL-C after eight weeks in step 2a trials 69 , 70 .…”
Section: Methodsmentioning
confidence: 99%
“…The PCSK9 gene is the latest discovered gene [ 22 ], but probably the most relevant one for FH management because its discovery allowed the identification of the molecular mechanism that is mostly targeted by innovative therapies based on its inhibition by monoclonal antibodies or small interfering RNAs [ 23 ]. The encoded protein is able to decrease the number of LDLRs on the plasma membrane through different mechanisms taking place either in the extracellular region or inside the cell.…”
Section: Genetics and Molecular Basismentioning
confidence: 99%
“…Bempedoic acid is another drug acting independently of LDLR used in HeFH patients; it is an inhibitor of the ATP citrate lyase, the enzyme transforming citrate into acetyl-CoA molecules used for fatty acid synthesis [ 40 ]. A recent paper has reviewed the new therapies for FH management in relation to the genetic status of patients [ 23 ].…”
Section: Genetics and Molecular Basismentioning
confidence: 99%
“…В частности, учитывая, что семейная гиперхолестеринемия в 85-95% обусловлена патогенными вариантами в гене LDLR, восстановление его функции с помощью генных препаратов может привести к устойчивому снижению концентрации ЛПНП и регрессии атеросклеротических заболеваний с минимальными побочными эффектами [64]. Наиболее эффективным и точным методом коррекции нуклеотидной последовательности целевых генов является редактирование генома с использованием системы CRISPR/Cas-9 [83,84]. В модели мышей с точечной мутацией гена LDLR применение системы CRISPR/Cas-9 позволяло добиться частичного восстановления экспрессии LDLR в гепатоцитах и, как следствие, значительного снижения концентрации общего холестерина, триглицеридов и ЛПНП в крови, а также уменьшения размеров уже образовавшихся атеросклеротических бляшек в аорте на 72% (в группе контроля не было зафиксировано уменьшения площади атеросклеротических бляшек) [84,85].…”
Section: перспективные направления исследованийunclassified
“…Наиболее эффективным и точным методом коррекции нуклеотидной последовательности целевых генов является редактирование генома с использованием системы CRISPR/Cas-9 [83,84]. В модели мышей с точечной мутацией гена LDLR применение системы CRISPR/Cas-9 позволяло добиться частичного восстановления экспрессии LDLR в гепатоцитах и, как следствие, значительного снижения концентрации общего холестерина, триглицеридов и ЛПНП в крови, а также уменьшения размеров уже образовавшихся атеросклеротических бляшек в аорте на 72% (в группе контроля не было зафиксировано уменьшения площади атеросклеротических бляшек) [84,85].…”
Section: перспективные направления исследованийunclassified